Comparing Arabic Linguistic Complexity with Other Languages in Relation to Cognitive Development - Nida Husnia Ramadhani; Rinda Eka Mulyani; Syaiful Mustofa; Yasser Abdullah Albudaya (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study examines the linguistic complexity of Arabic in morphology, semantics, and phonology, compared with other languages, and its impact on cognitive functions. Using a qualitative design and literature review method, the research draws on primary sources from Leipzig University journals and secondary sources from scholarly books, journals, and kutub al-turāth. Data were collected through document analysis and interpreted through reading, coding, and synthesis. The findings indicate that Arabic presents higher linguistic complexity in morphology, semantics, and phonology compared to English, German, and Hebrew. Furthermore, mastering Arabic contributes to the enhancement of cognitive functions, as its grammatical system stimulates both hemispheres of the brain. These results highlight not only the distinct linguistic structure of Arabic but also its cognitive benefits, suggesting that the study of Arabic can play a significant role in strengthening mental flexibility and intellectual capacity.